2022
DOI: 10.3389/fmicb.2022.825389
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of blaNDM– 1-Carrying Aeromonas caviae K433 Isolated From Patient With Community-Acquired Pneumonia

Abstract: To demonstrate the detailed genetic characteristics of a blaNDM–1-carrying multidrug-resistant Aeromonas caviae strain, the complete genome of the A. caviae strain K433 was sequenced by Illumina HiSeq and Oxford nanopore platforms, and mobile genetic elements associated with antibiotic resistance genes were analyzed by a series of bioinformatics methods. A. caviae K433 which was determined to produce class B carbapenemase, was resistant to most antibiotics tested except amikacin. The genome of K433 consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 40 publications
(42 reference statements)
0
20
0
Order By: Relevance
“…Currently, two reports related to bla NDM–1 -harboring A. caviae are available and both were isolated from the clinic in China. However, they were not associated with a biliary tract infection ( Luo et al, 2022 ; Xu et al, 2022 ). In addition, FAHZZU2447 carries other drug-resistance genes, including beta-lactams ( bla TEM– 1 B , bla NDM–1 , bla MOX– 6 , and bla OXA– 18 ), aminoglycosides [ aac(3)-IId , aph(6)-Id , aph(3 )-Ib ], tetracyclines [ tet(A) ], phenicols ( catA1 ), and sulfonamide ( dfrA5 , sul1 , sul2 ).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Currently, two reports related to bla NDM–1 -harboring A. caviae are available and both were isolated from the clinic in China. However, they were not associated with a biliary tract infection ( Luo et al, 2022 ; Xu et al, 2022 ). In addition, FAHZZU2447 carries other drug-resistance genes, including beta-lactams ( bla TEM– 1 B , bla NDM–1 , bla MOX– 6 , and bla OXA– 18 ), aminoglycosides [ aac(3)-IId , aph(6)-Id , aph(3 )-Ib ], tetracyclines [ tet(A) ], phenicols ( catA1 ), and sulfonamide ( dfrA5 , sul1 , sul2 ).…”
Section: Resultsmentioning
confidence: 92%
“…However, the current spread of NDM-1 was related to Enterobacterales and limited reports are available of NDM-1-carrying Aeromonas spp. ( Luo et al, 2022 ; Xu et al, 2022 ). To date, only two studies have reported on NDM-1-producing A. caviae , which were isolated from sputum and blood, and bla NDM–1 genes were located on the plasmid and chromosome, respectively ( Luo et al, 2022 ; Xu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…caviae K333 (accession no. CP084031 ) isolated from a human in China in 2020 (20). 5’- and 3’-ends of SEs and their 6-bp transposition footprint sequences in Aeromonas species isolates in this study are shown.…”
Section: Resultsmentioning
confidence: 99%
“…CP039832 ) (19) and A. caviae K333 (accession no. CP084031 ) (20), respectively. Moreover, the tet (X4) - containing region in NUITM-VA1 was also detected in the WCW1-2 chromosome, suggesting that these genetic structures around ARGs in Aeromonas species isolates herein described are not an unusual event.…”
Section: Resultsmentioning
confidence: 99%